Allocating Business Income between Capital and Labor under a Dual Income Tax : The Case of Iceland - Matheson, Thornton (IMF Working Papers; Working Paper ;, 2012)
In contrast to most Scandinavian countries, Iceland allocates the income of closely held businesses (CHBs) between capital and labor based on administratively set minimum wages rather than an imputed return to book assets.a This papera contrasts the relative tax burdens of the current minimum wage system with asset-based allocation methods, and finds that switching to an asset-based method could increase tax revenues from CHBs in a generally progressive manner.a Predictably, the shift would also raise the tax burden of skilled labor-intensive industries more than it would that of capital-intensive industries.